Protection of the Right to Be Forgotten on the Internet: The Study of Search Engine - Plumkoson, Paradee; Na Pibul, Auntika; Vanaphituk, Varaporn (Rajapark Journal, 2022)
The objectives of this study were: (1) to study the problems and methods to protect personal data and the right to be forgotten by the internet search engines in Thailand; (2) to analyze the principles and practices under Thai and foreign laws to protect the right to be forgotten by the internet search engines; and (3) to recommend a proper guideline for protecting the right to be forgotten by the internet search engines in Thailand. This study employed a qualitative research method by analyzing legal documents such as law textbooks, articles, theses, court judgments, and online data from both local and foreign sources. The study found that the Personal Data Protection Act B.E. 2562 provides uncovered and unclear provisions on the right to be forgotten by internet search engines. The study recommends promulgating the regulations for exercising rights and providing exemptions for the right to be forgotten by the internet search engines explicitly at the secondary law level as an appropriate guideline for protecting the right to be forgotten by the internet search engines in Thailand.